The Nonlinear Relationship Between Total Bilirubin and Coronary Heart Disease: A Dose-Response Meta-Analysis - Li, Chaoxiu; Wu, Wenying; Song, Yumeng; Xu, Shuang; Wu, Xiaomei (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Evidence suggests that total bilirubin has a protective effect on coronary heart disease (CHD), but the dose–response relationship remains controversial, and there is no meta-analysis to assess the relationship. Methods: As of October 1, 2021, relevant literature was selected from four databases (PubMed, Web of Science, Cochrane Library, Embase) by using a retrieval strategy. The dose-response curve between total bilirubin and CHD was fitted by restricted cubic spline. Stata 12.0 was used for statistical analysis. Results: A total of 170,209 (6,342 cases) participants from 7 prospective studies were analysed in our meta-analysis. We calculated the pooled relative risks (RRs) and 95% confidence intervals (CIs) for the association between serum bilirubin level and risk of CHD using random-effects models. Compared to the first quantile, the bilirubin level in the third quantile had a protective effect on the risk of CHD (RR, 0.90; 95% CI, 0.82-0.99). Restricted cubic spline functions depicted a U-type curve relationship between bilirubin (3.42-49μmol/L) and CHD (P linear <0.001). When the bilirubin level was in the range of 3.42μmol/L-13μmol/L, the protective effect of bilirubin on CHD was enhanced with increasing bilirubin levels. When the bilirubin level exceeded 13μmol/L, the protective effect of bilirubin weakened, and a dangerous effect gradually appeared with further increases in bilirubin levels. Conclusions: Compared with a low bilirubin level, a high bilirubin level has a protective effect on the risk of CHD, and there was a U-shaped dose–response relationship between them.